Language Features of the Translation of Pavel Bazhov’s Skaz the Malachite Casket to Polish Language - Матысяк, Юлия (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The aim of this work is the issue of the translations of Pavel Bazhov’s skaz The Malachite Casket to Polish Language. Only the most important aspects are considered. It is necessary to thoroughly investigate, whether the translator Czesław Jastrzębiec-Kozłowski managed to evoke the same or similar associations as the author. As the adequacy is one of the main aspects of the translation studies, it is appropriate to find and describe the exact translation method chosen by the translator. In the conclusion, the summary of the research is made.